2013
DOI: 10.1016/j.nicl.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular [11C]flumazenil binding for predicting postoperative outcome in individual patients with temporal lobe epilepsy and hippocampal sclerosis

Abstract: A third of patients with intractable temporal lobe epilepsy and hippocampal sclerosis (HS) are not seizure free (NSF) after surgery. Increased periventricular [11C]flumazenil (FMZ) binding, reflecting heterotopic neuron concentration, has been described as one predictor of NSF outcome at the group level. We aimed to replicate this finding in an independent larger cohort and investigated whether NSF outcome can be predicted in individuals.Preoperative [11C]FMZ summed radioactivity images were available for 16 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Patient details have been described in a previous study on [ 11 C]FMZ PET alone ( Yankam Njiwa et al, 2013 ). Briefly, sixteen patients (twelve women) fulfilled the criteria.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient details have been described in a previous study on [ 11 C]FMZ PET alone ( Yankam Njiwa et al, 2013 ). Briefly, sixteen patients (twelve women) fulfilled the criteria.…”
Section: Methodsmentioning
confidence: 99%
“…FMZ (RO 15-1788) was radiolabelled with 11 C via methylation ( Maziere et al, 1984 ). Unlabelled FMZ (0.01 mg/kg) and [ 11 C]FMZ (2.775 MBq/kg) were injected simultaneously ( Delforge et al, 1995 ), and twelve frames of increasing length were acquired over 55 min (for details, see ( Yankam Njiwa et al, 2013 )). Summed [ 11 C]FMZ radioactivity images were obtained from the attenuation and scatter corrected dynamic 3D series over the last five frames (20–55 min post injection), as these have been shown to yield particularly reliable measures ( Bouvard et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with normal MRI, about 40% had reduced 11 C-FMZ binding, a proportion similar to FDG-PET (Lamusuo et al, 2000). One group has found that increased periventricular FMZ binding may identify potentially epileptogenic heterotopias in patients with temporal-lobe foci and MTS, that may account in some cases for poor outcome after temporal lobectomy (Yankam-Njiwa et al, 2013). FMZ PET can also help elucidate the pathophysiology of epilepsy syndromes.…”
Section: Positron Emission Tomographymentioning
confidence: 99%